PENGARUH MENONTON ACARA TELEVISI TERHADAP PERKEMBANGAN BAHASA DAN SOSIAL EMOSIONAL PADA ANAK USIA 3-5 TAHUN - Enggal Sari Maduratna (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
*) Sekolah Tinggi Ilmu Kesehatan (STIKES) Ngudia Husada Madura Correspondence : Enggal Sari Maduratna Jl. R.E. Martadinata Bangkalan, Indonesia. LATAR BELAKANG Perkembangan bahasa merupakan indikator seluruh perkembangan anak. Kemampuan berbahasa sensitif terhadap keterlambatan sebab melibatkan pada kemampuan kognisi, sensori, psikologis, emosi, dan lingkungan disekitar anak. Sedangkan perkembangan sosial emosional anak ditandai dengan kematangan dalam hubungan sosial, atau proses belajar untuk pennyesuaian diri terhadap norma kelompok, moral dan tradisi dengan saling berkomunikasi dan bekerja sama. (Susanto,2011) Usia 3-5 tahun, anak mulai memasuki masa prasekolah. Masa ini ditandai dengan masa peka terhadap segala stimulasi yang diterimanya melalui pancaindra. Idealnya anak usia 3-5 tahun dapat menyatakan 1500-2100 kata, mengulang cerita P E N E L I T I A N I L M I A H ABSTRACT Language is the result of word-processing has expanded, while social emotional maturity is the achievement of children in their social relations . From the preliminary study of 10 children acquired 6 children (60%) have not been able to perform the duties of language development , such as has not been able to repeat the simple story and has not been able to communicate well . While 7 children (70%) do not have the confidence and self-sufficiency as well as interaction with peers are lacking. This study was to analyze the effect of watching television on the social and emotional development of language in children aged 3 -5 years The design of this study is Analytical Correlation with Cross Sectional approach . Independent variable is Watching television shows and the dependent variable is the development of language and social emotional. The population is 26 children with Proportional Stratified Random Sampling technique obtained a sample of 20 children. The collection tool is using questionnaires and KPSP. Univariate and bivariate analysis are using frequency distribution and statistical test Spearman Rank. Spearman Rank test results, showing that there is influence of watching television for language development of children aged 3-5 (ρ value = 0.001), there is influence of watching television for social emotional development of children aged 4-6 years (ρ value = 0.001) and almost half of children aged 3-5 watch television in weight category about of 45% . The results of this study can be used as inputs for parents that television viewing patterns can affect a child's development. With the result that parental supervision while watching television is needed to minimize the negative effects that may occur by limiting the time children watch television ≤ 2 hours per day